State taxation of interstate commerce and income flows: The economics of Neutrality - Alan D. Viard; Ryan Lirette (American Enterprise Institute (AEI), 2014)
Although the U.S. Supreme Court has long held that the Commerce Clause of the U.S. Constitution prohibits state taxes that discriminate against interstate commerce, it has failed to provide a clear explanation of which taxes are discriminatory. In this paper, we provide an economic analysis that distinguishes neutral and discriminatory state taxation of interstate commerce. We show that state taxes discriminate against interstate commerce if the combined tax burden on inbound and outbound transactions exceeds the tax on intrastate transactions. The analysis reveals that current state individual income tax systems systematically discriminate against interstate commerce.
Keywords: A; 330; tax reform; Interstate commerce